SAT0223 Dental implants are a treatment option in patients with sjögren's syndrome. (23rd January 2014) - Westhoff, G.; Doerner, T.D.O.R.A.C.I.; Cobarrubias, K.; Dietrich, T.; Zink, A.
Abstract : Background: Sjögren's syndrome (SS) is a chronic disease in which lymphocytes destroy moisture-producing glands, resulting in decreased production of tears and saliva. Due to xerostomia, patients with SS are at an increased risk for dental caries and are at the same time confronted with extraordinary difficulties to wear conventional dentures. Implant-supported prostheses could offer a solution. However, whether or not patients with SS are at an increased risk of implant failure has not been investigated. Given this lack of clinical evidence, dentists (and rheumatologists) may be less likely to recommend or even discourage SS patients from treatment with dental implants. Objectives: To assess the prevalence of dental implants in SS patients and to investigate the patient experience around dental implants. Methods: 153 female patients of an ongoing observational cohort study (77% primary, 23% secondary Sjögren's Syndrome) answered a 7-page oral health questionnaire dealing with mucositis, gingivitis, periodontitis, tooth loss and dental prostheses with an emphasis on dental implants. To enhance the validity of the self reports, some of the items were illustrated. Questions also pertained to 6 common comorbid conditions and 4 therapeutic agent groups that may interfere with bone remodeling. Data were compared with the reports of 68 age and gender matched friend controls. Results: Patients and controls were comparable in age (58±12 vs. 57±11 years) and education but differed substantially in the prevalence of toothache (48 vs. 15%) or bleeding of the gums within the previous 4 weeks (72 vs. 35%). Patients also reported more frequently gingivitis (46 vs. 21%) or periodontitis (24 vs. 10%) and having fewer teeth (21±7 vs. 23±5). Patients were more likely to have dental implants (13 vs. 8%). The 20 SS patients with dental implants had a mean number of 3.0±2.2 (median 2) implants ever. The mean age of the oldest implants was 5.1±6.3 years (median 3). Patients with dental implants were significantly older than patients without (64 vs. 57 years) and reported roughly as often conditions or therapies that are considered risk factors for implant therapy (osteoporosis 15 vs. 26%; diabetes 5 vs. 7%; cancer 15 vs. 12%; hyperthyreosis 5 vs. 12%; glucocorticoids 75 vs. 65%; bisphosphonates 5 vs. 12%; anticoagulants 15 vs. 14% or anticonvulsants 10 vs. 8%). Only 4 of the ever placed 60 implants had to be removed or replaced due to periimplantitis (7%). Except for the 4 patients who lost 1 implant each, all were highly satisfied with this dental solution (VAS 1.8); 19 out of 20 patients would recommend dental implants to other SS patients. Conclusions: Our investigation in a large group of patients with Sjögren's syndrome shows that dental implants are an option in many patients; even in some of those with additional comorbid risks. Our results may encourage patients, rheumatologists and dentists to consider implant supported prostheses instead of removable prostheses that may be difficult to tolerate in a dry mouth. Disclosure of Interest: None Declared